Natural rubber toughened epoxy/graphene conductive materials - Adrian, Lau Chee Onn (School of Material Engineering, University Malaysia Perlis, 2016)
In this research, graphene incorporated with epoxy composite was prepared using mechanical mixing technique with the density, flexural, fracture toughness, electrical conductivity, thermal stability and SEM morphology of the composite were studied. Graphene content was varied from, 0.2, 0.4, 0.6, 0.8, 1.0 vol% on the epoxy composite was studied. The addition of grahene into epoxy increases the density of the composite. The addition of graphene increases the flexural strength and modulus of the composite. The optimum graphene content in the epoxy composite was determined when 0.8 vol% of graphene added into the single phase epoxy composite. The effect of natural rubber in epoxy/NR/graphene composite was also studied based on similar testing. The density of the composite shows that with the addition of NR, the density of the composite reduces. At 5phr of rubber added into the conductive composite, the toughening effect can be observed through the fracture toughness properties. An increment of the electrical volume conductivity at 15phr of NR content in the epoxy/NR/graphene conductive composite compared to epoxy/graphene was observed.